Traditional Food Strategies Face Foreign Food Mediated By Product Innovation - Bintang Narpati; Eri Bukhari (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to analyze traditional food strategies in facing competition with foreign foods using Dynamic Capability Theory, with product innovation as a mediating variable in Micro, Small, and Medium Enterprises (MSMEs) culinary in Bekasi City. The research uses a quantitative approach with a survey design, where data is obtained through the distribution of questionnaires to culinary MSME actors in Bekasi City who were selected due to the rapid growth of the culinary sector. Data analysis was carried out using the Structural Equation Modeling (PLS-SEM) method, including validity, reliability, and path analysis tests to test the direct and indirect relationships between variables. The results of the study show that Digital Transformation and Knowledge Management as dynamic capabilities have a positive and significant effect on the business performance of culinary MSMEs. Product innovation acts as a mediator that strengthens the influence of these two variables on business performance, thereby increasing the competitiveness of traditional foods in the face of foreign food. Theoretically, this study strengthens the application of Dynamic Capability Theory in explaining the ability of culinary MSMEs to sense, capture, and reconfigure to maintain a competitive advantage. This study has a limited scope that only focuses on Bekasi City, so the results cannot be fully generalized to other regions, as well as limitations of secondary data that can affect the depth of analysis. However, this research makes an original contribution by integrating Digital Transformation and knowledge management within the framework of Dynamic Capability Theory with product innovation as a strategic mechanism, while highlighting efforts to revitalize traditional cuisine as a strategy to deal with the dominance of foreign food in the era of globalization.